Hubungan Konsumsi Makanan Sumber Lemak, Karbohidrat dan Aktivitas Fisik Dengan Rasio Lingkar Pinggang Panggul (RLPP) Pada Pengemudi Truk Po. Agm Kudus - Maila Try Haryati; Agustin Syamsianah; Erma Handarsari (Jurnal Gizi, 2014)
Fat deposits in the abdominal cavity that is known to be technically can be measured by the value of ratio between waist circumference and hip circumference, known as the waist -hip circumference ratio. The value of the  waist hip circumference ratio that reflect how many high fat deposits in the abdominal cavity. Consumption of fatty foods can increase the value of the  waist-hip  circumference ratio and the body weight. Decline in physical activity is also related to increased the  waist circumference. The general aim of this study is to analysis  the relationship of food consumption, resource of fats, carbohydrates and physical activity with the value of  waist-hip circumference ratio at PO AGM Kudus teamster. The typeof the study is an explanatory research with crossectional approach .The study was done at 30 teamster, all the number of PO. AGM teamsters There are no possible extraction of samples. The Kolmogorov-Smirnov Test will be used to test the normality distribution of the data of fat consumption level, karbohydrat consumption level and the physical activity.. The result of the test showed that all of the data are not normally distribution. Based of the result, we use the Spearman Rank Test to analysis the correlation between fat consumption level, karbohydrat consumption level and the physical activitywith the value of waist-hip circumference ratio. The results showed that 53.3 % of respondents are 36-45 years old , 56.7 % of responden have a high school education, 70 % of responden consume the more categories level of fat, 53.3 % of responden consume the good categorylevel of carbohydrat, 63.3 % of responden have a median category level of  physical activity, and  90 % of res ponden have a value of waist-hip  circumference ratio on risk of degenerative disease. There is relationship between fat consumption level with waist hip circumference ratio ( p-value = 0,004 ), no relationship between the level of carbohydrate consumption with waist hip circumference ratio ( p-value = 0,326 ), and no relationship between physical activity with the rate at Waist belt circumference ( p-value = 0,064 ). Conclution : The waist-hip circumference related with the level of fat consumption,but not related with the level of carbohydrate consumption and physical activity.  Good as possible  the teamsters  eat a balanced diet, that’s sufficientof  energy,  carbohydrate, protein, fat, and the other micronutrients contai. to support the teamster physical activity and prevent the risk of degenerative diseases